St KItts and Nevis 1983-1984 membership directory and buyers guide (St Kitts-Nevis Chamber of Industry & Commerce BasseterreKN, 1984)
Alphabetically lists members of the St Kitts-Nevis chamber of industry and commerce. Contains classified alphabetical listing of member businesses of the chamber. Outlines St Kitts-Nevis's investment incentives.
IDS